Faktor-Faktor Yang Mempengaruhi Kejadian Kecacatan Pada Pasien Kusta: Literature Review - Prima, Ashar; Irham, Faisal; Astuti, Puji; Fauji, Achmad (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:  This study aims was to  explain t the factors that influence the incidence of disability in leprosy patients.. Methods: This study was using literature review as research design. This Literature using Google schoolar,Portal garuda and ProQuest as database search. The literature used article were in english and Indonesian Published around 2011-2020, is approved then selected and ReviewedResults:   There are 13 articles was faunded. 10 articles on Google Schoolar, 2 found on the garuda portal, 1 ProQuest.  The results of the study contained 11 factors, namely the type of MB leprosy, duration of leprosy, reaction to leprosy, number of affected nerves, delay in treatment/diagnosis, social economy, gender, occupation, education level, regularity of treatment, and self-care that affect the incidence of disability in leprosy patients.Conclusion:   The factors that influence the incidence of disability in leprosy patients are divided into 3 groups, namely demographic factors, internal factors and external factors